Legalidad, proporcionalidad y equidad tributaria del artículo 31 fracción IV de la Constitución: ¿son derechos humanos? - Morales Serafín, J. Jesús (Universidad Michoacana de San Nicolás de Hidalgo, 2015)
The constitutional principles of taxation imposed in the United States of Mexico, have evolved in response to each of the historical stages of the nation today in the light of the constitutional reform of 6 on the amparo and 10 June 2011, let’s consider them as human rights. While it is true that Article 31 paragraph IV Constitution is outside the top 29 articles that watched individual guarantees, today human rights and guarantees, no less certain is that the maximum court of the country, decreed mid 80's law firm, that the principles of legality, proportionality and the injured tax equity, individual rights are transgressed, human rights today. This has been affirmed the Plenum of the Supreme Court of the nation that, although Article 31 of the Constitution, which establishes the requirements of proportionality and equality and rights for all taxpayers, is not in the chapter on individual rights the lesion of the right itself is a violation of securities where the taxes decreed the Legislature are notoriously exorbitant and ruinous. The Congress recently legislated, a package of tax reforms to various federal systems (Legislature., 2013.), The legislative process resulted in the establishment of no new taxes, but in expanding concepts that previously were not taxed in the field of Income Tax, Value Added Tax and Special Tax on Production and Services; if the federal legislature did not comply in its endeavor reformer constitutional principles of taxation set out in section IV of article 31 of the Constitution, individuals affected by the legal institution of amparo may request protection and protection of Justice of the Union an obvious violation of their human rights.

Los principios constitucionales de la tributación establecidos en los Estados Unidos Mexicanos, han tenido una evolución atendiendo a cada una de las etapas históricas de la nación, hoy a la luz de la reforma constitucional del 6, sobre el juicio de amparo y la del 10 de junio de 2011, permite considerarlos como Derechos Humanos. Si bien es cierto, este artículo 31 fracción IV constitucional se encuentra fuera de los primeros 29 artículos que contemplaban garantías individuales, hoy derechos humanos y sus garantías, no menos cierto es, que el máximo órgano jurisdiccional del país, decretó a mediados de los años 80´s en jurisprudencia firme, que dichos principios de legalidad, proporcionalidad y equidad tributaria al lesionarse, se trasgreden garantías individuales, hoy derechos humanos. Así lo ha sostenido el Pleno de la Suprema Corte de Justicia de la nación que, si bien el artículo 31 de la Constitución, que establece los requisitos de proporcionalidad y equidad como derechos de todos contribuyentes, no está en el capítulo relativo a las garantías individuales, la lesión de este derecho sí es una violación de garantías cuando los tributos que decreta el Poder Legislativo son notoriamente exorbitantes y ruinosos. El Congreso de la Unión legisló recientemente, un paquete de reformas fiscales a diversos ordenamientos federales (Legislatura., 2013.),el proceso legislativo derivó no en el establecimiento de nuevas contribuciones, pero sí en la ampliación de conceptos que anteriormente no se encontraban gravados en materia del Impuesto Sobre la Renta, Impuesto al Valor Agregado e Impuesto Especial Sobre Producción y Servicios.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Fiscal
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2015-0112; Tributación; Derechos; Contribuciones; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6055